Population Structure of Lassa Mammarenavirus in West Africa - Diego Forni; Manuela Sironi (Viruses, 2020)
Lassa mammarenavirus (LASV) is the etiologic agent of Lassa fever. In endemic regions in West Africa, LASV genetic diversity tends to cluster by geographic area. Seven LASV lineages are recognized, but the role of viral genetic determinants on disease presentation in humans is uncertain. We investigated the geographic structure and distribution of LASV in West Africa. We found strong spatial clustering of LASV populations, with two major east–west and north–south diversity gradients. Analysis of ancestry components indicated that known LASV lineages diverged from an ancestral population that most likely circulated in Nigeria, although alternative locations, such as Togo, cannot be excluded. Extant sequences carrying the largest contribution of this ancestral population include the prototype Pinneo strain, the Togo isolates, and a few viruses isolated in Nigeria. The LASV populations that experienced the strongest drift circulate in Mali and the Ivory Coast. By focusing on sequences form a single LASV sublineage (IIg), we identified an ancestry component possibly associated with protection from a fatal disease outcome. Although the same ancestry component tends to associate with lower viral loads in plasma, the small sample size requires that these results are treated with extreme caution.